Comparing plasmonic electrodes prepared by electron-beam lithography and electrochemical reduction of an Au (iii) salt: application in active plasmonic devices. (27th January 2016) - Nguyen, Van-Quynh; Schaming, Delphine; Martin, Pascal; Lacroix, Jean-Christophe
Abstract: This work describes two different methods for obtaining electrodes covered with gold nanoparticles: electron-beam lithography and electroreduction of an Au (iii ) salt by chronoamperometry. Localized surface plasmon resonances of these different electrodes have been compared. In a second step, these plasmonic AuNP electrodes were covered with an ultrathin organic film of bisthienylbenzene which displays a reversible voltage-dependent switch between conducting and insulating states. The effect of this conductance switch on the plasmonic properties of the AuNPs has been studied.